Hematobium schistosomiasis control for health management of labor force generation at Nkhotakota and Lilongwe in the Republic of Malawi—assumed to be related to occupational risk - Nobuyuki Mishima (Tropical Medicine and Health, 2019)
Abstract Background In Malawi, hematobium schistosomiasis is highly endemic. According to previous studies, countermeasures have been conducted mainly in school-aged children. In this study, we focused on the age groups, which are assumed to be major labor force generation. Hematobium schistosomiasis is supposed to be related to occupational activities in schistosome-endemic countries because of its infectious route. We chronologically followed the transition of schistosome egg-positive prevalence before and after mass drug administration of praziquantel (MDA) by using a urine filtering examination. We also analyzed the effectiveness of urine reagent strips from the cost perspective. Results The egg-positive prevalence was 34.3% (95% CI 28.5–40.5) just before MDA in June 2010 and the highest prevalence was in the age of twenties. The egg-positive prevalence reduced to 12.7% (95% CI 9.2–17.3, p < 0.01) 8 weeks after the first MDA and the prevalence reduced to 6.9% (95% CI 4.6–10.0, p < 0.01) after the second MDA in August 2011. The egg-positive prevalence after MDA in 2013 was reduced from 3.8% (95% CI 2.1–6.9) to 0.9% (95% CI 0.3–3.4) and p value was 0.050. Using urine reagent strips after MDA, the positive predictive value decreased, but the negative predictive value remained high. The cost of one urine reagent strip and one tablet of praziquantel were US$0.06 and US$0.125 in 2013 in Malawi. If the egg-positive prevalence is 40%, screening subjects for MDA using urine reagent strips, the cost reduction can be estimated to be about 24%, showing an overall cost reduction. Conclusions MDA of praziquantel can assuredly reduce schistosome egg-positive prevalence. The combination of MDA and urine reagent strips could be both a practical and cost-effective countermeasure for hematobium schistosomiasis. It is key to recognize that hematobium schistosomiasis could be considered a disease that is assumed to have some concern with occupational risk at Nkhotakota and Lilongwe in Malawi. From this point of view, it is very important to manage workers’ health; the sound labor force generation is vital for economic growth and development in these areas and countries.